Arthroscopic reduction and fixation of partial posterior wall acetabular fractures - Aprato, Alessandro; Sallam, Adell; Di Benedetto, Paolo; Giaretta, Stefano; Massè, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Reduction and fixation of partial posterior wall fracture is usually performed with an open posterolateral approach. When the fragment may be fixed without a plate (with screws only), reduction and fixation may be also achieved via hip arthroscopy. To our knowledge no study described this technique. Aim of our study is to describe the surgical technique and to present the achieved outcomes and the occurred complications.Methods: Six cases of arthroscopic fixation of partial posterior wall fracture have been reviewed for the purpose of this study. Patients were treated arthroscopically if the fragment was not bigger than 25% of the posterior wall. Patient demographic, injury, and surgical variables as well as complications were recorded and retrospectively evaluated. Radiographic outcome was scored according to Matta’s criteria on postoperative radiographs and clinical outcomes were evaluated with the modified Harris hip score.Results: Fracture reduction was classified as anatomic on post-operative x-rays in all patients. The mean clinical score was 98 points at one year follow-up. No patient developed symptomatic femoral head AVN, none had heterotopic ossification. In one patients a screw breakage occurred without clinical complications.Conclusions: Arthroscopic reduction and fixation of partial posterior wall fracture is an effective treatment and showed good outcomes if a careful patients’ selection is done.